Depth of invasion in oral squamous carcinoma – More to this than meets the eye!. (March 2023) - Merchant, Yash P; Shetty, Sameep; Jayaraj, Rama; Gopalakrishnan, D
Highlights: Accurate pre-operative assessment of depth of Invasion in oral squamous cell carcinoma is challenging. While it appears that Magnetic Resonance Imaging is the best imaging modality to measure DOI, USG has its own unique applications. Multiparametric MRI should be employed for pre-operative DOI assessment. DWI prevents upstaging due to peritumoral oedema.